PENGEMBANGAN MULTIMEDIA UNTUK PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK (PAK) - Katarina Hingi Tukan; Aloysius Mering; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aimed to produce a professional 3D pageflip learning multimedia. This method used the research and development method with the ADDIE design. The development procedure was the pre-development stage, the development stage and the trial, revision and evaluation stage. The results of the media expert validation obtained an average value of 3.73. The results of the material expert validation obtained an average value of 3.81. The results of the design expert validation obtained an average value of 3.88 with very valid criteria (range of values 0-4). The average posttest learning outcomes of students was 86.07 ≥75 (KKM). The increase is also seen from the paired two-sample t test showing the t value (17.577) ≥ t table (2.05954) there was a difference before and after using professional 3D pageflip multimedia improves student learning outcomes. Keywords: Acqusition of learning outcomes, Development, Professional 3D pagefli